Arctigenin prevents the progression of osteoarthritis by targeting PI3K/Akt/NF‐κB axis: In vitro and in vivo studies. Issue 7 (24th February 2020) - Tang, Shangkun; Zhou, Weijun; Zhong, Xinyang; Xu, Jianchen; Huang, Huasong; Zheng, Xinnan; Zhang, Jingkang; Yang, Shuyue; Shang, Ping; Tang, Qian; Liu, Haixiao
Abstract: Osteoarthritis (OA), which is principally featured by progressive joint metabolic imbalance and subsequent degeneration of articular cartilage, is a common chronic joint disease. Arctigenin (ATG), a dietary phyto‐oestrogen, has been described to have potent anti‐inflammatory effects. Nevertheless, its protective effects on OA have not been clearly established. The target of our following study is to evaluate the protective effects of ATG on IL‐1β–induced human OA chondrocytes and mouse OA model. Our results revealed that the ATG pre‐treatment effectively decreases the level of pro‐inflammatory mediators, such as prostaglandin E2 (PGE2), nitrous oxide (NO), inducible nitric oxide synthase (iNOS), cyclooxygenase‐2 (COX‐2), IL‐6 and tumour necrosis factor alpha (TNF‐α) in IL‐1β–induced human chondrocytes. In addition, ATG protects against the degradation of extracellular matrix (ECM) under the stimulation of IL‐1β and the possible mechanism might be connected with the inactivation of phosphatidylinositol‐3‐kinase (PI3K)/Akt/nuclear factor‐kappa B (NF‐κB) axis. Furthermore, a powerful binding capacity between ATG and PI3K was also uncovered in our molecular docking research. Meanwhile, ATG may act as a protector on the mouse OA model. Collectively, all these findings suggest that ATG could be utilized as a promising therapeutic agent for the treatment of OA.